FINANCING OF HOUSING CONSTRUCTION WITH THE HELP OF VENTURE FUND - Рубцова, Оксана (SWorldJournal, 2020)
The essence of financing of construction projects in Ukraine is analyzed and the search for new methods for conditions of tax optimization of activity of participants of investment and construction process is made. The current state and features of taxati